The effects of leaf shear breaking load on the feeding value of perennial ryegrass for sheep : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, Palmerston North, New Zealand - Inoue, Tatsushi (Massey University, 1992)
Reducing physical resistance has been thought to be a key factor to increase efficiency of masticatory breakdown of forage, which may lead to faster rumen fractional outflow rates (FOR) and consequently to increased voluntary feed intake and hence improved feeding value (FV). Two selections of perennial ryegrass (PRG) were selected for low (LS) and high leaf shear breaking load (HS) based on the maximum load required to shear across the leaf, i.e. leaf shear breaking load (LSBL). The series of experiments were conducted to investigate the effects of LSBL on the FV of PRG for sheep. LSBL, morphological and anatomical parameters were measured on the LS and HS PRG selections grown under the optimum climatic conditions. LSBL for the LS PRG selection was approximately 41 % lower the HS PRG selection. However, the LS selection had shorter leaf lengths, narrower leaf widths and narrower leaf cross-sectional area (CSA) than the HS selection. Therefore, in leaf shear strength (LSS), the LS selection was estimated to be approximately 27 % less resistant to shear than the HS selection per unit of CSA. The lower LSS in the LS selection is due to the lower concentration of sclerenchyma tissues in leaf CSA compared with the HS selection. However, the differences in the total shear load required to breakdown a unit dry weight of leaves to 1 x 1 mm·particle size, namely, leaf index of masticatory load (IML) between the selections were influenced by the differences in m orphological characteristics of leaves between the two PRG selections. Comparisons were made between the LS and HS PRG selections in the efficiency of mastication by sheep on particle breakdown. There were no major effects of reduced LSBL in PRG on the efficiency of mastication during eating and during rumination. Although the LS PRG selection was approximately 29 % lower in LSBL than the HS PRG selection, the difference for the two PRG selections in IML was almost nil. Effects of LSBL in PRG on rumen fractional outflow rate (FOR) and apparent digestibilities were investigated in sheep fed at restricted feed intake levels. There were no effects of reduced LSBL on FOR, although the LS PRG selection was approximately 39 and 12 % lower than the HS PRG selection in LSBL and IML, respectively. The digestibility of the cellulose fractions was approximately 16 % lower in the LS PRG selection than the HS PRG selection. The leaf morphology in PRO may affect the efficiency of fibre digestibility. Two field trials were conducted to test the hypothesis that LSBL in PRG improves FOR and leads to higher voluntary feed intake, and hence achieves improved live weight gain and wool production, namely FV. Although the LS PRG selection had 25-30 % lower LSBL than the HS PRG selection, live weight gain and wool production of sheep were not improved by reduced LSBL. FOR in sheep showed no indications of difference and voluntary feed intake was similar between the animals grazing the LS and HS PRO selections. The lack of difference in IML between the LS and HS PRG selection can be considered as a main reason for this. The hypothesis, that reduced LSBL in PRG would improve its FV, was therefore rejected. In conclusion, there were no major effects of reduced LSBL in PRG on efficiency of masticatory particle breakdown, and consequently, FOR, feed intake and hence FV in sheep. This is due to the lack of selection effect of PRG in IML. IML is a determining fac tor for the efficiency of mastication both during eating and rumination. The selection of PRG for a lower IML will, therefore, be necessary in I order to increase efficiency of masticatory particle breakdown, FOR and hence FV of PRG.
Keywords: Forage; Perennial ryegrass; Sheep feeding and feeds; Ryegrass digestion